Pengaruh Profesionalisme,Akuntanbilitas, Kompetensi, Independensi Auditor, dan Due Profesional Care Terhadap Kualitas Audit Pada Kantor Akuntan Publik di Medan - Desi Wulan Sari; Shita Tiara (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The purpose of this study was to determine the effect of Professionalism, Accountability, Competence, Auditor Independence, and Due Professional Care on Audit Quality. Data collection was carried out by distributing questionnaires whose validity and reliability had been tested. This research was conducted at 18 public accounting firms in Medan. The number of samples was 66 auditors with purposive sampling technique. The results showed that partially professionalism has a significant effect on audit quality at the accounting firm in Medan. Accountability has a significant effect on audit quality at the accounting firm in Medan. Competence has a significant influence on audit quality at the accounting firm in Medan. Auditor independence has no significant effect on audit quality at the accounting firm in Medan. Due professional care has a significant influence on audit quality at the accounting firm in Medan. The results also show that simultaneously professionalism, accountability, competence, auditor independence, due professional care simultaneously have a significant influence on audit quality at the accounting firm in Medan.